Anionic sigmatropic-electrocyclic-Chugaev cascades: accessing 12-aryl-5-(methylthiocarbonylthio)tetracenes and a related anthra[2,3-b]thiophene - Burroughs, Laurence; Ritchie, John; Ngwenya, Mkhethwa; Khan, Dilfaraz; Lewis, William; Woodward, Simon (Beilstein Journal of Organic Chemistry, 2015)
1,4-Diols resulting from the double addition of ArCCLi (Ar = Ph, substituted phenyl, 2-thienyl) to ortho-C6H4(CHO)2 undergo cascades to tetracenes on simple admixture of LiHDMS, CS2 and MeI. Acene formation proceeds by [3,3]-sigmatropic rearrangement of xanthate anions followed by 6π electrocyclisations. The reactions are terminated by E2 or anionic Chugaev-type eliminations. Structural packing motifs and electronic properties are reported for the tetracenes.
Keywords: allenes; anionic Chugaev rearrangement; anionic sigmatropic rearrangement; tetracene properties; X-ray structures

Organic Electronics: Emerging Concepts and Technologies - Cicoira, F.; Santato, C. (Wiley-VCH, 2013)

Organic Electronics: Materials, Processing, Devices and Applications - So, F. (CRC Press, 2010)

(untitled) - Wang, C.; Dong, H.; Hu, W.; Liu, Y.; Zhu, D. (Chem. Rev., 2012)

(untitled) - Takimiya, K.; Osaka, I.; Nakano, M. (Chem. Mater., 2014)

(untitled) - Bendikov, M.; Wudl, F.; Perepichka, D. F. (Chem. Rev., 2004)

(untitled) - Qu, H.; Chi, C. (Curr. Org. Chem., 2010)

(untitled) - Müller, A. M.; Avlasevich, Y. S.; Schoeller, W. W.; Müllen, K.; Bardeen, C. J. (J. Am. Chem. Soc., 2007)

(untitled) - Yagodkin, E.; Douglas, C. J. (Tetrahedron Lett., 2010)

(untitled) - Papagni, A.; Trombini, C.; Lombardo, M.; Bergantin, S.; Chams, A.; Chiarucci, M.; Miozzo, L.; Parravicini, M. (Organometallics, 2011)

(untitled) - Gu, X.; Luhman, W. A.; Yagodkin, E.; Holmes, R. J.; Douglas, C. J. (Org. Lett., 2012)

(untitled) - McGarry, K. A.; Xie, W.; Sutton, C.; Risko, C.; Wu, Y.; Young, V. G., Jr; Brédas, J.-L.; Frisbie, C. D.; Douglas, C. J. (Chem. Mater., 2013)

(untitled) - Mamada, M.; Katagiri, H.; Sakanoue, T.; Tokito, S. (Cryst. Growth Des., 2015)

(untitled) - Okamoto, T.; Nakahara, K.; Saeki, A.; Seki, S.; Oh, J. H.; Akkerman, H. B.; Bao, Z.; Matsuo, Y. (Chem. Mater., 2011)

(untitled) - Lin, Y.-C.; Lin, C.-H. (Org. Lett., 2007)

(untitled) - Rodríguez, D.; Castedo, L.; Domínguez, D.; Saá, C. (Org. Lett., 2003)

(untitled) - Chen, M.; Chen, Y.; Liu, Y. (Chem. Commun., 2012)

(untitled) - Tomita, K.; Nagano, M. (Chem. Pharm. Bull., 1968)

(untitled) - Woodward, R. B.; Hoffmann, R. (Angew. Chem., Int. Ed. Engl., 1969)

(untitled) - Evenseck, J. D.; Thomas, B. E., IV; Spellmeyer, D. C.; Houk, K. N. (J. Org. Chem., 1995)

(untitled) - Zhao, Y. H.; Abraham, M. H.; Zissimos, A. M. (J. Org. Chem., 2003)

(untitled) - McDaniel, D. H.; Brown, H. C. (J. Org. Chem., 1958)

Name Reactions - Li, J. J. (Chugaev elimination, 2009)

(untitled) - Sun, H.; DiMagno, S. G. (J. Am. Chem. Soc., 2005)

(untitled) - Bellville, D. J.; Wirth, D. D.; Bauld, N. L. (J. Am. Chem. Soc., 1981)

(untitled) - Lutz, R. P. (Chem. Rev., 1984)

(untitled) - Denmark, S. E.; Marlin, J. E.; Rajendra, G. (J. Org. Chem., 2013)

(untitled) - Rigaudy, J.; Capdevielle, P. (Tetrahedron, 1977)

(untitled) - Braga, D.; Jaafari, A.; Miozzo, L.; Moret, M.; Rizzato, S.; Papagni, A.; Yassar, A. (Eur. J. Org. Chem., 2011)

(untitled) - Casian, A.; Stockholm, J. G.; Dusciac, V.; Nicic, V. (J. Nanoelectron. Optoelectron., 2009)

(untitled) - Nowell, X. H.; Barnett, S. A.; Christensen, K. E.; Teat, S. J.; Allan, D. R. (J. Synchrotron Radiat., 2012)